2021
DOI: 10.1002/cbin.11718
|View full text |Cite
|
Sign up to set email alerts
|

Blocking connexin43 hemichannels prevents TGF‐β2 upregulation and epithelial–mesenchymal transition in retinal pigment epithelial cells

Abstract: Epithelial–mesenchymal transition (EMT) occurs when polarised epithelial cells change to a mesenchymal phenotype. EMT plays a role in several chronic conditions, including ocular diseases with retinal pigment epithelium (RPE) EMT associated with retinal diseases such as diabetic retinopathy (DR). Here, EMT results in breakdown of the blood‐retinal barrier (BRB) leading to sub‐retinal fluid deposition and retinal detachment. Previous studies have shown that blocking connexin43 (Cx43) hemichannels can protect ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Indeed, here, it is shown that the canonical markers of EMT such as, for instance, ACTA2 and FnI [ 10 , 30 ] are reduced by the treatment of the cells with OTX008. Worthy of note is that the EMT of polarized RPE cells is a process activated under pathological circumstances, such as inflammation, wound healing, and carcinogenesis, enabling epithelial cells to obtain an enhanced migration ability and increase their production of extracellular matrix components, leading to RPE dysfunction [ 31 ]. Loss of RPE functional integrity is the base for development of numerous retinal diseases, including inherited cone-rod degenerations, inherited macular degeneration, age-related macular degeneration, and proliferative vitreoretinopathy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, here, it is shown that the canonical markers of EMT such as, for instance, ACTA2 and FnI [ 10 , 30 ] are reduced by the treatment of the cells with OTX008. Worthy of note is that the EMT of polarized RPE cells is a process activated under pathological circumstances, such as inflammation, wound healing, and carcinogenesis, enabling epithelial cells to obtain an enhanced migration ability and increase their production of extracellular matrix components, leading to RPE dysfunction [ 31 ]. Loss of RPE functional integrity is the base for development of numerous retinal diseases, including inherited cone-rod degenerations, inherited macular degeneration, age-related macular degeneration, and proliferative vitreoretinopathy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also found that the expression of Cx43 was increased in ECs induced by low laminar shear stress. It was widely depicted that Cx43 accelerated the EMT process [ 37 , 38 ], in which TGF signaling pathways play a vital role [ 39 ]. It is notable that TGF signaling pathways have been well established in the initiation of EndMT process [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Connexin hemichannel blockers represent a promising future therapeutic option in the treatment of nephropathy and retinopathy. Research to date is persuasive and highlights promising beneficial effects of Cx43 inhibition on inflammation, tissue integrity and fibrosis [ 180 , 201 , 202 ]. However, the field requires further research to determine the effectiveness and efficacy of drugs and the long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…As with onset and progression of tubulointerstitial fibrosis [ 167 ], the breakdown of the retinal pigment epithelium is associated with disassembly of junction proteins, namely ZO-1, E-cadherin, β-catenin and occludin and ultimately induction of EMT [ 179 ]. In fact, EMT of RPE cells is considered an initiating trigger in the loss of epithelial integrity and is driven by glucose-evoked changes in TGFβ [ 180 ]. Moreover, a recent study by Lyon et al identified that inflammation coupled with glycaemic damage mediates EMT of the RPE via aberrant Cx43 mediated hemichannel activity [ 50 ], whilst Peptide 5 blocked loss of ZO-1 expression and restores RPE permeability as measured by transepithelial resistance [ 125 ].…”
Section: The Therapeutic Potential Of Blocking Cx43 In Diabetic Retinopathymentioning
confidence: 99%